2017
DOI: 10.1186/s12936-017-1819-7
|View full text |Cite
|
Sign up to set email alerts
|

The malaria testing and treatment landscape in mainland Tanzania, 2016

Abstract: BackgroundUnderstanding the key characteristics of malaria testing and treatment is essential to the control of a disease that continues to pose a major risk of morbidity and mortality in mainland Tanzania, with evidence of a resurgence of the disease in recent years. The introduction of artemisinin combination therapy (ACT) as the first-line treatment for malaria, alongside policies to promote rational case management following testing, highlights the need for evidence of anti-malarial and testing markets in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…One option may be to permit the licensing of unregistered pharmacies through accreditation programmes, or through partnerships with the public sector, as a means to increase access to appropriate malaria case management services. Evidence from other countries has demonstrated that the registration, training and supervision of the private sector, can lend to improvements in malaria commodity ACT availability, distribution and provider performance [ 20 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…One option may be to permit the licensing of unregistered pharmacies through accreditation programmes, or through partnerships with the public sector, as a means to increase access to appropriate malaria case management services. Evidence from other countries has demonstrated that the registration, training and supervision of the private sector, can lend to improvements in malaria commodity ACT availability, distribution and provider performance [ 20 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malaria RDTs have also been deployed to reach half of the population so far, and health workers have been trained in using them [ 4 , 6 ]. Recent surveys have reported that availability of malaria testing was 83% in the public sector where more than 70% of the suspected cases were tested [ 4 , 7 ]. This was not the case in the private sector where there was only 16% of testing available [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent surveys have reported that availability of malaria testing was 83% in the public sector where more than 70% of the suspected cases were tested [ 4 , 7 ]. This was not the case in the private sector where there was only 16% of testing available [ 7 ]. Diagnosis availability and compliance to diagnosis results are major factors to reach rational use of treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Malaria is still a major cause of mortality and morbidity in sub-Saharan Africa including Tanzania [ 7 9 ]. The government of Tanzania has extensively provided and is scaling up free distribution of long lasting insecticidal nets [ 10 , 11 ], free anti-malarial [ 12 ] and rapid diagnostic kits [ 13 ] in all health facilities across the country as a strategy for strengthening malaria control. Vector control constitute a major component of the global strategy for malaria control [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%